Education to the Community about the Concept of Waste Banks, Green Economy, and Money Supply - Dewi Mahrani Rangkuty; Anwar Suhut; Suryani Sajar; Rahmadhani Fitri; Yanti Br Naibaho (International Journal of Economics, Commerce, and Management, 2025)
Education on the Concept of Waste Bank, Green Economy, and Circulating Money to the Community is carried out in order to understand how its application becomes a household income opportunity, for example by becoming a new source of income from saving household waste that has been applied so that it is able to read the economic and environmental problems that occur. How the impact of the Waste Bank on income from household waste. Which is related to improving household welfare through community knowledge / understanding related to Waste Bank, Green Economy, and Circulating Money. From this community service, the results show that with the existence of the Waste Bank, the application of the Green Economy concept can be seen from the collection of household waste easily collected at the Waste Bank, the community becomes a customer, has savings, withdraws money, then continues consumption shopping from the money, which means there is buying and selling activity in the market because there is money circulating in the community. This affects economic activity in the Medan Belawan sub-district.